Long-Term Outcome of 118 Acute Total Brachial Plexus Injury Patients Using Free Vascularized Ulnar Nerve Graft to Innervate the Median Nerve - Lin, Jennifer An-Jou; Lu, Johnny Chuieng-Yi; Chang, Tommy Nai-Jen; Sakarya, Ahmet Hamdi; Chuang, David Chwei-Chin (Journal of Reconstructive Microsurgery, 2022)
Background The restoration of finger movement in total brachial plexus injuries (BPIs) is an ultimate challenge. Pedicled vascularized ulnar nerve graft (VUNG) connecting a proximal root to distal target nerves has shown unpredictable outcomes. We modified this technique by harvesting VUNG as a free flap to reinnervate median nerve (MN). We analyzed the long-term outcomes of these methods.Methods From years 1998 to 2015, 118 acute total brachial plexus patients received free VUNG to innervate the MN. Patients were followed up at least 5 years after the initial surgery. Donor nerves included the ipsilateral C5 root (25 patients) or contralateral C7 root (CC7 = 93 patients). Recovery of finger and elbow flexion was evaluated with the modified Medical Research Council system. Michigan Hand Score and Quick-DASH were used to represent the patient-reported outcomes.Results For finger flexion, ipsilateral C5 transfer to MN alone yielded similar outcomes to MN + MCN (musculocutaneous nerve), while CC7 had significantly better finger flexion when coapted to MN alone than to MN + MCN. Approximately 75% patients were able to achieve finger flexion with nerve transfer alone. For elbow flexion, best outcome was seen in the ipsilateral C5 to MCN and MN.Conclusion In acute total BPI, the priority is to identify the ipsilateral C5 root to innervate MN, with concomitant innervation of MCN to establish the best outcomes for finger and elbow flexion. CC7 is more reliable when used to innervate one target (MN).Level of evidence: III.
Keywords: free vascularized ulnar nerve graft; total brachial plexus injury; contralateral C7; ipsilateral C5